2010
DOI: 10.1590/s0366-69132010000300010
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cr2O3 on the mullittization of di-phasic Al2O3-SiO2 gel

Abstract: Diphasic Al2O3-SiO2 gel was synthesized by sol-gel route from inorganic salts following aqueous phase colloidal interaction and the effect of Cr2O3 additive on the formation of mullite ceramics from this diphasic gel was investigated. The gel powder was thoroughly characterized by chemical analysis, measurement of surface area, bulk density and FTIR spectroscopy. The calcined gel was compacted with Cr2O3 additives in three different proportions (ca. 1, 2 and 3 wt%) and heat treated at different elevated temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition to the strength, Hideki Yoshida et al observed that triaxial porcelain glaze with incorporated silver-clay as antimicrobial agent also showed a good antimicrobial activity using Escherichia coli (E. coli) as test organism [15]. In several literatures, authors reported the enhancement of mullite growth during the high temperature sintering of different clay materials (most important constituents of porcelain) [10][11][12]16,17] and alumino-silicate precursors [18][19][20][21][22][23] in the presence of different oxides and metal ions. The effect of the copper ions and oxides of vanadium and copper on the formation of mullite from both clay and alumino-silicate precursor and their effect on the strength of mullite were very well studied [11,12,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the strength, Hideki Yoshida et al observed that triaxial porcelain glaze with incorporated silver-clay as antimicrobial agent also showed a good antimicrobial activity using Escherichia coli (E. coli) as test organism [15]. In several literatures, authors reported the enhancement of mullite growth during the high temperature sintering of different clay materials (most important constituents of porcelain) [10][11][12]16,17] and alumino-silicate precursors [18][19][20][21][22][23] in the presence of different oxides and metal ions. The effect of the copper ions and oxides of vanadium and copper on the formation of mullite from both clay and alumino-silicate precursor and their effect on the strength of mullite were very well studied [11,12,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Ca-free insulators consisting of high-purity alumina or mullite are commercially available, 11),12) but they are much more expensive than CaSiObased compounds. Therefore, insulators consisting of CaSiO are widely used especially in the field of large-scale heating apparatuses.…”
Section: )8)mentioning
confidence: 99%
“…It is revealed that Al 2 O 3 -Cr coatings possess improved toughness combined high hardness [2]. And formation of Cr 2 O 3 -Al 2 O 3 solid solution can improve strength and toughness of Al 2 O 3 [3]. Researches on preparation of Al 2 O 3 -Cr coatings on steel by aluminothermic process with revealed that temperatures higher than 1200 ºC are usually required for Aluminum -Cr 2 O 3 system [4].…”
mentioning
confidence: 99%